18th International Congress of Metrology 2017
DOI: 10.1051/metrology/201708004
|View full text |Cite
|
Sign up to set email alerts
|

A full-scale thermo-hydraulic simulator for the characterization of building heat cost allocation methods

Abstract: Abstract. An innovative heat accounting method for apartment buildings, named EcoThermo, based on the estimation of water flow rates at each radiator by thermo-hydraulic modelling of the hot water distribution system, has been developed in the framework of the EU Programme FP7-SME-2012. In order to validate this approach and to compare it with conventional Heat Cost Allocators (HCA), a full-scale thermo-hydraulic simulator has been recently built at INRIM. This INRIM test facility represents a real-scale hot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Optimum installation position of HCAs at a radiator height of about 60% has been demonstrated Bozzini et al [121] Test on HCAs in a "vertical" hot water distribution network of 10 radiators of different types, materials and installation conditions Authors found relative deviations with respect to the reference share of radiator heat consumption, up to 30% When heat consumptions are shared, compensation of systematic errors occur as far as the radiators within the same building are similar for type, material, shape, dimensions, installation, operative conditions Saba et al [27] Metrological reliability of HCAs and ITCs Uncertainty of heat sharing of about 11% at critical conditions could decrease to about 3% in optimal ones Dell'Isola et al [28] On field experimental comparison of direct and indirect heat accounting systems (HCAs and ITCs) HCA accuracy is comparable with the one of DHMs (share error in the whole heating season of about 3.0% for HCAs vs 1% for DHMs), Share error in the whole heating season of about 7.1% for ITC-DDC and of about 8.2% for ITC-TC, error becomes unacceptable (up to 12.4%) for heating plants handled differently or in case of very low energy consumption.…”
Section: Michnikows Ki and Deska [120] Optimum Installation Of Hcasmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimum installation position of HCAs at a radiator height of about 60% has been demonstrated Bozzini et al [121] Test on HCAs in a "vertical" hot water distribution network of 10 radiators of different types, materials and installation conditions Authors found relative deviations with respect to the reference share of radiator heat consumption, up to 30% When heat consumptions are shared, compensation of systematic errors occur as far as the radiators within the same building are similar for type, material, shape, dimensions, installation, operative conditions Saba et al [27] Metrological reliability of HCAs and ITCs Uncertainty of heat sharing of about 11% at critical conditions could decrease to about 3% in optimal ones Dell'Isola et al [28] On field experimental comparison of direct and indirect heat accounting systems (HCAs and ITCs) HCA accuracy is comparable with the one of DHMs (share error in the whole heating season of about 3.0% for HCAs vs 1% for DHMs), Share error in the whole heating season of about 7.1% for ITC-DDC and of about 8.2% for ITC-TC, error becomes unacceptable (up to 12.4%) for heating plants handled differently or in case of very low energy consumption.…”
Section: Michnikows Ki and Deska [120] Optimum Installation Of Hcasmentioning
confidence: 99%
“…The alternative use of DHMs and IHASs implies some consequences in terms of consumer protection. Accuracy of IHASs could range from 3.0% to 12.4% [26] and up to 30% [27] while in different operating conditions it ranges from about 2.7 % to about 11.7 % [28]. Moreover, only DHMs are currently regulated by legal metrology [29], therefore they can be used both for measuring thermal energy at the point of supply and also for sub-metering of energy consumption within the building.…”
Section: Introductionmentioning
confidence: 99%